China's Millennials : The Want Generation - Fish, Eric (Lanham Rowman & Littlefield, 2016)
Eric Fish provides compelling portraits of young Chinese as they struggle to cope with their country's wrenching socioeconomic and demographic transition after years of lofty expectations. He deftly captures their hopes, disillusionment, and rebellion in a system that is scrambling to keep them in line as they increasingly refuse to conform.
Include Illustrations, Notes and Index.
The Want Generation.
Keywords: China -- Youth in development -- Generation Y